Proceedings of the 8th International Conference on Evaluation of Novel Approaches to Software Engineering 2013
DOI: 10.5220/0004569302540259
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Engineering with Agent-Oriented Models

Abstract: We have repeatedly encountered in industry-oriented research projects missing stakeholder input and invalid requirements. This has prompted us to come up with a novel idea to mitigate the problem of collecting and documenting requirements. The essence of the approach proposed by us lies in linking two kinds of artifacts proposed by agent-oriented modeling-goal models and behavioral scenarios-to user stories. In the paper, we first provide short overviews of requirements engineering in agile software developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Studies focusing on detecting ambiguity generally applied means of automatic interpretation of natural language requirements (e.g., [24,28,37,[39][40][41]) or the transformation of natural language requirements into models (e. g., [36,[42][43][44][45][46][47]). Studies that aimed to reduce ambiguity in natural language requirements proposed grammatical restrictions (e.g., [26,[48][49][50]), the standardization of sentence structures (e.g., [32,51,52]), and models or ontologies supporting requirements formulation (e.g., [53][54][55][56][57]).…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies focusing on detecting ambiguity generally applied means of automatic interpretation of natural language requirements (e.g., [24,28,37,[39][40][41]) or the transformation of natural language requirements into models (e. g., [36,[42][43][44][45][46][47]). Studies that aimed to reduce ambiguity in natural language requirements proposed grammatical restrictions (e.g., [26,[48][49][50]), the standardization of sentence structures (e.g., [32,51,52]), and models or ontologies supporting requirements formulation (e.g., [53][54][55][56][57]).…”
Section: Related Workmentioning
confidence: 99%
“…Inconsistency is a problem that occurs within a set of related user stories if interpretations conflict, hence it is a problem of ambiguity. The reviewed studies showed that inconsistency may result in requirements being incomplete [41,43,46,47,49,53,73,74,76] and systems being non-compliant [24,43,45,46,49,55,57,[69][70][71][72][73][74][75][76].…”
Section: Inconsistencymentioning
confidence: 99%
See 3 more Smart Citations